How developing communities of practice can accelerate gender research - Maraka, Joshua. M (CGIAR GENDER Impact Platform, 2022)
‘’Gender research can be very exciting, but sometimes lonely, as often there is only one gender researcher in each project,” proposed Arwen Bailey, a knowledge sharing specialist at The Alliance of Bioversity International and the International Center for Tropical Agricul-ture (CIAT). Bailey was introducing a discussion among CGIAR gender researchers on how communities of practice (CoPs) can help accelerate and improve gender research, as part of a three-day GENDER Science Exchange conference that took place in October in Nairobi, Kenya.